Analisis Pengaruh Makro Ekonomi Terhadap Indeks Harga Saham Syariah Indonesia - Iskandar, Dadang Ishak; Hasanuddin, Hasanuddin; Sari, Romida Rifiana (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to analyze the effect of macroeconomic variables on the Indonesian Sharia stock price index. The macro variables in this study are inflation and the rupiah exchange rate. This research is quantitative research with an associative approach. The samples in this study were taken from January 2018 to December 2022. Data analysis used the classical assumption test and multiple linear regression with partial tests. The results of this study indicate that inflation has a positive and significant effect on the Islamic stock price index, while the rupiah exchange rate has a negative and significant effect on the Islamic stock price index in Indonesia. Meanwhile, the coefficient of determination is 47.9 percent. Keywords : Inflation, Rupiah Exchange Rate, Indonesian Syariah Stock Index